2003
DOI: 10.1029/2002jd003248
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic‐scale transport of reactive nitrogen over the western Pacific in spring

Abstract: [1] Pathways of synoptic-scale uplifted transport of pollutants from East Asia and their effects on chemical distributions of NO y species are investigated based on a subset of the aircraft data obtained during the NASA Transport and Chemical Evolution over the Pacific (TRACE-P) experiment, conducted in February-April 2001. Meteorological and chemical analyses indicate that 73% of the uplifted transport was associated with warm conveyor belts (WCBs) and convective outflow (COF), which transported air masses st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
106
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(122 citation statements)
references
References 50 publications
13
106
1
2
Order By: Relevance
“…Many previous studies have used CO as a tracer to examine the patterns and mechanisms of Asian outflow to the Pacific, and much of the attention has thus far been paid to springtime (Liu et al, 2003;Fuelburg et al, 2003;Liang et al, 2004Liang et al, , 2005Liang et al, , 2007Miyazaki et al, 2003;Koile et al, 2003;Holzer et al, 2005). They found that the major process responsible for the export of Asian anthropogenic pollution to the western Pacific during spring is frontal lifting to the free troposphere (FT) ahead of southeastward-moving cold fronts and transport in the boundary layer (BL) behind the cold front.…”
Section: China Outflowmentioning
confidence: 99%
See 3 more Smart Citations
“…Many previous studies have used CO as a tracer to examine the patterns and mechanisms of Asian outflow to the Pacific, and much of the attention has thus far been paid to springtime (Liu et al, 2003;Fuelburg et al, 2003;Liang et al, 2004Liang et al, , 2005Liang et al, , 2007Miyazaki et al, 2003;Koile et al, 2003;Holzer et al, 2005). They found that the major process responsible for the export of Asian anthropogenic pollution to the western Pacific during spring is frontal lifting to the free troposphere (FT) ahead of southeastward-moving cold fronts and transport in the boundary layer (BL) behind the cold front.…”
Section: China Outflowmentioning
confidence: 99%
“…The deeper convection in summer bringing CO to higher altitudes with more efficient export is the important factor for higher export efficiency in summer. Miyazaki et al (2003) and Koike et al (2003) studied the export of anthropogenic reactive nitrogen and sulfur compounds from the East Asia region and the synoptic-scale transport mechanisms of the two chemical species over the western pacific in spring. Specifically, they calculated quantitatively the export efficiency of NO y and SO x using the P-3B and DC-8 aircraft observation data over the western Pacific during the TRACE-P campaign.…”
Section: Spring (Mam)mentioning
confidence: 99%
See 2 more Smart Citations
“…Model simulations showed that the PSEA biomass-burning pollutants were lifted from the surface near their source region by deep convection. These pollutants were then transported along the warm conveyor belts ahead of cold fronts to the northwestern Pacific at altitudes above 2 km (Carmichael et al, 2003;Liu et al, 2003;Miyazaki et al, 2003;Lin et al, 2009).…”
Section: Y Jian and T-m Fu: Injection Heights Of Springtime Biomasmentioning
confidence: 99%